Design and synthesis of a novel series of cyanoindole derivatives as potent γ-secretase modulators. Issue 14 (15th July 2019) - Bischoff, François P.; Velter, Adriana Ingrid; Minne, Garrett; Pieters, Serge; Berthelot, Didier; De Cleyn, Michel; Gijsen, Harrie J.M.; Macdonald, Gregor; Surkyn, Michel; Van Brandt, Sven; Van Roosbroeck, Yves; Zavattaro, Chiara; et al.
Graphical abstract: Abstract: The discovery, design and synthesis of a new series of GSMs is described. The classical imidazole heterocycle has been replaced by a cyano group attached to an indole nucleus. The exploration of this series has led to compound 26-S which combined high in vitro and in vivo potency with an acceptable drug-like profile.